Energy Trajectory Efficiency In Europe And Eurasia A Dynamic Panel Data Models Analysis - Guellil, Mohammed Seghir; Khedir, Oussama; Brahimi, Assia (Finance and Business Economies Review, 2019)
World energy consumption alludes to the aggregate energy utilized by all of human civilization. As per the International Energy Agency (IEA), the worldwide energy consumption has been becoming relentlessly finished the last decade; where it constitutes one of the main parts with the quickest developing on the planet. This investigation examinations the connection between global energy consumption and diverse perspectives. The outcomes demonstrate a noteworthy way, which is a cointegrating connection between energy consumption and the variables package. The outcomes likewise show bidirectional, unidirectional and neutral causality between energy consumption and a few factors, which could be a decent tool to prioritize the allocation of assets crosswise over businesses to guarantee a superior fiery strategy by and large and monetary results.